Removed asphalt can be used as a component of constructed soils for urban greenery - Rompato, Bianca; Rossi, Riccardo; Giagnoni, Laura; Mastrolonardo, Giovanni; Argenti, Giovanni; Staglianò, Nicolina; Nuñez, Remigio Paradelo; Certini, Giacomo (Journal of soils and sediments, 2025)
Purpose This study deals with the possibility of adding some of the removed and appropriately crushed bituminous conglomerate (here called simply asphalt), as well as compost from municipal solid waste recycling, to urban depaved soils to be used as green areas, to reduce disposal costs. Methods For this purpose, we conducted a 5-month long pot experiment testing five treatments with different proportions of asphalt (30% v/v, 20% v/v, and 10% v/v), compost (20% v/v and 10% v/v), and excavated urban soil making up the remainder. A mix of grasses commonly used in urban green infrastructures was sown and monitored over time in terms of growth rate and morphological traits. Additionally, the possible release of heavy metals and polycyclic aromatic hydrocarbons (PAHs) was evaluated by analysing both the constructed soils and the leachates, to ascertain if the rules requiring asphalt to be landfilled rather than reused (at least partially) in green infrastructure are reasonable. Results Asphalt did not have any apparent negative impact on grass growth. The release of heavy metals and PAHs was minor and anyway below the national legal standards. All substrates with asphalt showed similar or even better physico-chemical and biochemical features than the excavated soil alone, while compost addition enhanced all the grass morphometric traits investigated. Conclusions This study suggests that, in areas desealed for urban re-greening, utilizing a portion of the removed asphalt in place, once appropriately crushed, together with soil and compost could be a feasible and safe approach.